2010
DOI: 10.4049/jimmunol.1000572
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Simian Immunodeficiency Virus-Specific Cytotoxic CD4+ T Cells and Increased Humoral Responses Correlate with Control of Rebounding Viremia in CD8-Depleted Macaques Infected with Rev-Independent Live-Attenuated Simian Immunodeficiency Virus

Abstract: Indian rhesus macaques infected with the Rev-independent live-attenuated SIVmac239 strains control viremia to undetectable levels, have persistent but low cellular and humoral anti-SIV responses, and show no signs of immune deficiency. To analyze the immune mechanisms responsible for viral control, five macaques infected at day 1 after birth were subjected to CD8+ cell depletion at 6.7 y postinfection. This resulted in viremia increases to 3.7–5.5 log10 RNA copies, supporting a role of CD8-mediated responses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 69 publications
(91 reference statements)
2
21
0
1
Order By: Relevance
“…The inhibitory mechanism of CD8 ϩ T cells on CD4 ϩ T cell cytotoxicity is also not understood, but similar findings were made in CD8-depleted, simian immunodeficiency virus (SIV)-infected macaques, where GzmB-expressing CD4 ϩ T cells were shown to expand (51). One possible explanation is that CD8 ϩ Tregs might play a role.…”
Section: Fig 5 Fv Loads After T Cell Depletion Splenocytes From Diffmentioning
confidence: 90%
“…The inhibitory mechanism of CD8 ϩ T cells on CD4 ϩ T cell cytotoxicity is also not understood, but similar findings were made in CD8-depleted, simian immunodeficiency virus (SIV)-infected macaques, where GzmB-expressing CD4 ϩ T cells were shown to expand (51). One possible explanation is that CD8 ϩ Tregs might play a role.…”
Section: Fig 5 Fv Loads After T Cell Depletion Splenocytes From Diffmentioning
confidence: 90%
“…Subsequent analysis showed that this lack of control may be due to the depletion of cytolytic CD4 ϩ T cells. In contrast, depletion of CD8 ϩ T cells and control of SIV viremia was associated with the emergence of humoral and cytolytic CD4 ϩ T cell responses (23). Beyond natural HIV infection, the ability to degranulate upon antigenic recognition and release effector molecules such as perforin and granzyme B has been shown to be a key feature of antigen-specific CD4 ϩ T cells in other viral infections such as CMV and hepatitis C (26), as well as in cases of cancer (27) and after vaccination (2,28).…”
Section: Although Cd4mentioning
confidence: 91%
“…ϩ T cells exhibit a host of different helper functions that contribute to the HIV-specific immune response, a growing body of evidence supports the idea that direct cytolytic effector activity by CD4 ϩ T cells is also important for HIV control and clearance (1,23,24). Indeed, besides HIV-specific CD8 ϩ T cells, the emergence of HIV-specific cytolytic CD4 ϩ T cells during acute HIV infection has been linked to control of viral replication (5,25).…”
Section: Although Cd4mentioning
confidence: 97%
“…SIV-infected macaques controlling viral replication were depleted of CD8 T cells, leading to increased viremia that was rapidly controlled despite the lack of SIV-specific CD8 T cells (113). Viral control was associated with antibody responses and expansion of circulating SIV-specific CD4 T cells that were CD45RA− CD28+ CD95+ CCR7− and expressed GzmB (113).…”
Section: Infections In Which Cd4 Ctl Are Protectivementioning
confidence: 99%